Preparation and characterization of poly (methyl methacrylate) / irradiated - 50% epoxidized natural rubber based solid electrolytes / Zayana Saif - Saif, Zayana (2009)
Previously poly (methyl methacrylate) has exhibited high ionic conductivity when it was fabricated in gel form. However, this gel electrolyte exhibited poor mechanical stability. Therefore, in order to obtain a better mechanical stability of PMMA based electrolyte, it needs to be prepared in a film form. Unfortunately, this PMMA film is brittle. Therefore, in this study it was blended with 50% epoxidized natural rubber that has soft elastomeric, good elasticity and adhesion properties. Due to the nature of the rubber to form inter-chain cross-linking that may limits the segmental motion of the polymer electrolyte system, therefore, it was irradiated under UV light at various irradiation time to reduce the number of inter-chain cross-linking in the rubber system. All the PMMA / iENR 50 films were prepared by solvent casting technique and the films were then characterized using optical polarizing microscopy, differential scanning calorimetry (DSC), thermo-gravimetric analysis / differential thermo-gravimetric analysis (TGAIDTA), Fourier Transform Infrared (FTIR) and impedance spectroscopy. From the DSC analysis, it was found that the Tg of un-irradiated ENR 50 was reduced from -25°C to -26°C when it was irradiated for 30 seconds indicating that it has the highest chain flexibility as a result of breaking of the inter-chain cross-linking. Therefore, it can be concluded that it requires only 30 seconds of UV irradiation to heal the inter-chain cross-linking in the ENR 50 system. The reduction of the number of inter-chain crosslinking has been confirmed by the reduction of the intensity of the OH band at 34403424 cm-1 followed by the increased in the intensity of the epoxy ring at 1255 cm-1. When this 30iENR 50 was blended with PMMA, it produced the most flexible freestanding film as compared to un-irradiated and other irradiated ENR 50 systems. Furthermore, this PMMA / 30iENR 50 exhibited the highest conductivity of 1.03 X 10-4 S/cm due to the flexibility of the polymer chain and the formation of a less viscous phase that favor the migration of lithium ion in the blend matrix. The addition of PC plasticizer further enhanced the conductivity of the PMMA / 30iENR 50 / LiCF3S03 electrolyte to 1.16 X 10.3S/cm. The ionic conduction of the doped PMMA / 3OiENR 50 system was found to obey the Arrhenius behaviour in which the migration of ions was thermally assisted. Interestingly, there were two activation energies (Ea) were observed from the doped PMMA / 30iENR 50 electrolytes in which the Ea2 at higher temperature was less than Ea1 observed at lower temperature due to the change of the phase from crystalline to an amorphous phase at 70°C. This was confirmed from the DSC thermogram of the blend system. However, for the plasticized PMMA / 30iENR 50 / LiCF3SO3 electrolyte, the ionic conduction was due to the segmental motion of the polymer indicating that the presence of PC enhanced the mobility of the polymer.